Compassionate care in nursing: A hybrid concept analysis - Vahid Zamanzadeh; Leila Valizadeh; Azad Rahmani; Mansour Ghafourifard (Tehran University of Medical Sciences, 2017)
Background & Aim: Although compassionate care is recognized as a core component of nursing care, there is not still a precise definition about this complex and challenging concept. This study aimed to analyze the concept of compassionate care in nursing using a hybrid model. Methods & Materials: A three-phase hybrid model (theoretical, field work, and final analysis) was used in this study. In the theoretical phase, the concept of compassionate care was searched in main databases from 2000 to 2016. In the field work phase, in-depth, face to face interviews were done with 11 nurses. The content analysis method was used to analyze the data. Final analysis was done in the last phase. Results: The results of the final analysis showed that compassionate care is a process in which nurses interactively communicate with patients, try to explore patients' concerns by putting themselves in their positions and understanding their situations, and do their utmost to eliminate these concerns. Conclusion: According to this concept analysis, the constructive interaction between nurse and patient is one of the most important features of compassionate care that has not been mentioned in previous definitions. Also in this study, the nurses emphasized that they did their best to resolve the patients' concerns. Therefore, the current study could be the basis for future studies in the area of compassionate care.